(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper focuses facts on both sides of the relationship between empowerment and growth. First, it shows that poverty and lack of opportunity create differences between men and women so that as economic growth reduces poverty, women’s situation improves on two aspects: the first, as poverty is decreased, the condition of everyone, including women, improves and the second is that inequality of gender declines when poverty decreases. However, economic growth is not enough to achieve full equality between men and women. Policy steps are also important in order to achieve gender equality. It is clear that such policy action is warranted if the empowerment of women also encourages further growth and the launching of a virtuous cycle.